Synthesis, crystal structures, DNA interactions, and antitumor activity of two new dinuclear copper(ii) complexes with thiazole ligand. Issue 63 (16th December 2021) - Zeng, Zhenfang; Cai, Jiehui; Li, Fuyan; Weng, Yanying; Huang, Qiuping; Yang, Honglan; Huang, Qiuchan; Wei, Youhuan
Abstract : Two new dinuclear copper(ii ) complexes, [Cu(ambt)2 (cnba)4 ] (a) and [Cu(ambt)2 (clba)4 ] (b) were synthesized with 2-amino-6-methoxybenzothiazole (ambt) as the main ligand. Abstract : Two new dinuclear copper(ii ) complexes, [Cu(ambt)2 (cnba)4 ] (1 ) and [Cu(ambt)2 (clba)4 ] (2 ) were synthesized with 2-amino-6-methoxybenzothiazole (ambt) as the main ligand. The structures of the two complexes were characterized by single-crystal XRD. The binding between CT-DNA (calf thymus DNA) and the complexes was evaluated by viscometry, electronic absorption, and fluorescence spectroscopy, and the binding constants were calculated using the Stern–Volmer equation. The complexes were intercalatively bound to CT-DNA, and [Cu(ambt)2 (clba)4 ] having a greater binding constant than [Cu(ambt)2 (cnba)4 ]. The two complexes had better antitumor properties against HepG2 (human hepatocellular carcinoma), A549 (human lung carcinoma), and HeLa (human cervical carcinoma) tumor cell lines than their respective ligands and cisplatin. Furthermore, [Cu(ambt)2 (clba)4 ] had a stronger inhibitory ability on the three types of tumor cells than [Cu(ambt)2 (cnba)4 ], which is congruent with the binding power of the complexes with DNA. Flow cytometry revealed that [Cu(ambt)2 (cnba)4 ] and [Cu(ambt)2 (clba)4 ] could trigger apoptosis or necrosis, arrest the HepG2 cell cycles, and cause G0/G1-phase cells to accumulate.